Analysis of Communication Ethics Philosophy of Bhuppa' Bhappu' Ghuru Rato in Madura - Aminullah, Aminullah; Nurhadi, Agus (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The Madura philosophy of Bhuppa' Bhappu' Ghuru Rato is applied in the daily lives of Madura people as a form of communication ethics. But with globalization these shifts are starting to occur in the daily lives of Madurese people. This research aims to find out and analyze the form of application of communication ethics in the application of Bhuppa' Bhappu' Ghuru Rato's philosophy as well as the main factors that make this shift in communication ethics. This research method is qualitative with an ethnographic approach. Observation, interviews and documentation are data collection techniques. The data will then be analyzed by processing the data, grouping the data, and sorting and selecting the appropriate data. The results show that the forms of implementing communication ethics in the philosophy of Bhuppa' Bhappu' Ghuru Rato are the use of the Madura language level of speech in everyday life. In the era of globalization, a shift in communication ethics occurs, a decrease in the use of Madura speech levels, a reduction in social hierarchical orientation and the loss of face-to-face interaction. This is a factor in globalization, urbanization and the culture of wandering as well as modernization in the current education system.